Personal Characteristics Associated with Working After Disability Onset for People with Visual Impairments. (March 2021) - McKnight, Zhen S.; Crudden, Adele; McDonnall, Michele C.
Introduction: This study utilized data from the 2014 Survey of Disability and Employment (SDE) to examine personal characteristics that influenced employment after disability onset for people who are visually impaired (i.e., those who are blind or have low vision). Method: The selected sample from the SDE data set included 131 individuals who are visually impaired, had disability onset after age 14 years, and worked before their disability onset. Logistic regression was used to examine working after disability onset associated with age at disability onset, years since disability onset, gender, race, education, receipt of government disability benefits, self-reported health, encouragement received to work, additional disabilities, and the interaction between age at disability onset and years since disability onset. Results: Persons who were female, received government benefits, and had multiple disabilities were less likely to work after disability onset; persons who had more sources of encouragement were more likely to work after disability onset. Age at disability onset interacted with time since disability onset; as age increased, odds of working after disability onset increased but only for persons who had their disability for at least 4 years. Discussion: Persons with newly acquired disabilities may need time to adjust to their disability and learn new skills that allow them to continue employment. Information about how employment may influence receipt of government benefits would be helpful to persons evaluating their options regarding continuing employment. Implications for practitioners: A person who has not worked after recent disability onset may be adjusting to life with a disability and may return to work in the future. Encouragement to work from both service providers and family members made a meaningful difference in employment retention after disability onset, and this is an area that vocational rehabilitation professionals can influence.